Here's the question you clicked on:
boomzoom
Let f(x) = x + 8 and g(x) = x2 - 6x - 7. Find f(g(2)).
first what is g(2)?
what do you mean "????"
your question said what is g(2) that how the poblem was given
First you must find g(2) by putting into the equation for g(2). Then you would take the step as to put what g(2) = into the f(x) equation.
By putting 2 into the equation for g, excuse me. Its a multi-step equation.
When you see g(2), that means solve g(x) where x = 2. \[\Large g(x) = x^{2}-6x-7\] \[\Large g(2) = 2^{2}-(6*2)-7= ?\]
f(g(2) ) means you find g(2) then substitute that to x in f(g(2) )
Note: Alternatively you could solve it all at once (but that may confusing right off the bat): \[\Large f(g(2)) = (x^{2}-6x-7)+8 = x^{2}-6x+1\]
What did you get for g(2)?
Correct. Since g(2)=-15, that means f(g(2)) = f(-15). \[\Large f(x) = x+8\] \[\Large f(-15) = -15+8 = ?\]
Let f(x) = x + 8 and g(x) = x2 - 6x - 7. Find f(g(2)). first find g(2) then once you find that plug that to f(x)